Persepsi Mahasiswa terhadap Penerapan Gallery Learning dalam Praktikum Mata Kuliah Berbasis Teknologi: Sebuah Studi Deskriptif - Wulandari, Nourma Pramestie; Salsabila, Nilza Humaira; Primajati, Gilang (FKIP Universitas Mataram, 2024)
The aim of this study is to explore the views of Mathematics Education students regarding the necessity of using varied learning models, such as Gallery Learning, in technology-based course practicums. This research employs a descriptive quantitative method involving 28 students as respondents. Based on the results of the distributed questionnaire, the majority of students agreed that incorporating varied learning models like Gallery Learning is essential for technology-based course practicums. Students also expressed increased enthusiasm and active participation during practicums using this model. The findings indicate that Gallery Learning enhances students' understanding of practicum materials, fosters critical thinking, and boosts motivation to learn. Overall, students felt that this varied learning model significantly improved the quality of their learning experience.